Anticipatory action in self-defence essence and limits under international law - Tibori Szabó, Kinga; SpringerLink (Online service). (The Hague, The Netherlands Berlin T.M.C. Asser Press Distributed by Springer-Verlag, 2011)
The legality of pre emptive strikes is one of the most controversial questions of contemporary international law. At the core of this controversy stands the temporal dimension of self-defence: when and for how long can a state defend itself against an armed attack? Can it resort to armed force before such an attack occurs? Is anticipatory action covered by the rules of self-defence or should it be treated as a different concept? This book examines whether anticipatory action in self-defence is part of customary international law and, if so, under what conditions. The pre-Charter concept of anticipatory action is demarcated and then assessed against post-Charter state practice. Several instances of self-defence ? both anticipatory and remedial ? are examined to elucidate the rules governing the temporal dimension of the right. The Six-Day War (1967), the Israeli bombing of an Iraqi reactor (1981), the US invasion of Iraq (2003) and other instances of state practice are given thorough attention. The innovative mark of this book is its comprehensive focus on the temporal dimension and, particularly, the anticipatory aspect of self-defence. By way of conclusion, the definition and limits of anticipatory action in self-defence are incorporated into an accessible formula. The book is highly recommended to academics and legal advisers ? ministries of foreign affairs and defence ? as well as to international organizations, military academies and journalists. Kinga Tibori Szabó is presently working at the International Criminal Tribunal for the Former Yugoslavia, The Hague, The Netherlands. With a Foreword by Pieter H. Kooijmans, former judge in the International Court of Justice.
Introduction -- Part I. Pre-Charter customary law on self-defence -- Self-defence in ancient and medieval natural-law -- Self-defence as a measure short of war -- Self-defence as an exception to the prohibition of war -- The right of self-defence and the drafting of the UN Charter -- The temporal dimension of self-defence at the time of the Charter -- Part II. Post-Charter customary law on self-defence -- The right of self-defence in the judgments of the Nuremberg and Tokyo Tribunals -- Self-defence in state-to-state conflicts -- Self-defence and weapons of mass destruction -- Self-defence against non-state actors -- The interpretation of self-defence and the United Nations -- The temporal dimension of post-charter self-defence -- Part III. Anticipatory action in self-defence and international customary law-- The legality of anticipatory action in self-defence -- The limits of anticipatory action in self-defence.
Electronic reproduction.
Keywords: Self-defense (International law); Preemptive attack (Military science); Electronic books